Gender Inequalities in Employment of Parents Caring for Children With Autism Spectrum Disorder in China: Cross-Sectional Study - Yanan Zhao; Huiyun Fan; Yanan Luo; Rong Zhang; Xiaoying Zheng (JMIR Pediatrics and Parenting)
Abstract BackgroundThe increasing need for child care is placing a burden on parents, including those with children with autism. ObjectiveThe aim of this study was to examine the employment status of Chinese mothers and fathers with children with autism spectrum disorder (ASD), as well as to investigate the factors that affected their employment decisions. MethodsAn online national survey was completed by the parents of 5018 children and adolescents with ASD aged 2-17 years (4837 couples, 181 single mothers, and 148 single fathers). The dependent variable was employment status—whether they kept working or quit to take care of their child. The independent variables were those characterizing the needs of the child and the sociodemographic characteristics of the family. ResultsThe employment rate of mothers with children and adolescents with ASD was 37.3% (1874/5018), while 96.7% (4823/4988) of fathers were employed. In addition, 54.3% (2723/5018) of mothers resigned from employment outside the home to care for their children, while only 2.8% (139/4988) of fathers resigned due to caring obligations. Mothers’ employment was positively associated with their single marital status, lower educational level, and having assistance from grandparents. Having the grandparents’ assistance was positively associated with fathers’ employment. ConclusionsGender inequalities in employment exist in China. Mothers caring for children with ASD had lower workforce participation than fathers. More female-friendly policies and a stronger gender equality ideology would be of benefit to Chinese society.